2003
DOI: 10.1243/030932403770735917
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-mode fatigue crack propagation in thin T-sections under plane stress

Abstract: Data that can be used in the fatigue analysis of¯at T-section bars subjected to axial loading and local restraint are presented. The paper describes how ®nite element analysis has been used to obtain stress ®elds in the vicinity of a crack or crack-like¯aw introduced into the ®llet (i.e. high-stress) region of the component. The effect of both the position and inclination of the crack has been investigated. The inclination of the crack to the transverse direction is varied in such a way that a combination of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…4. Due to lack of creep crack study in T-section component at first, some elastic finite element analyses have been done and the results were compared with data available [5] . This comparison confirmed that the level of mesh refinement and the use of the crack tip elements in current study would provide accuracy to within ±3%.…”
Section: Finite Element Analysis Of the Cracked Componentsmentioning
confidence: 99%
See 2 more Smart Citations
“…4. Due to lack of creep crack study in T-section component at first, some elastic finite element analyses have been done and the results were compared with data available [5] . This comparison confirmed that the level of mesh refinement and the use of the crack tip elements in current study would provide accuracy to within ±3%.…”
Section: Finite Element Analysis Of the Cracked Componentsmentioning
confidence: 99%
“…To determined stress concentration factor K t in a T-section component subjected to loaded projection the following relation ship was reported [5] , using a statistical multiple nonlinear regression model: In a similar way to [5] , the following equation is derived for the stress concentration factor of a T-section component under remote loading condition:…”
Section: Stress Concentration Factormentioning
confidence: 99%
See 1 more Smart Citation